PENGARUH PENGUNGKAPAN SUKARELA GCG TERHADAP HUBUNGAN ANTARA UKURAN DEWAN KOMISARIS, DAN NILAI PERUSAHAAN DI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI IDX - Almatius Setya Marsudi (Fakultas Ekonomi Universitas Pekalongan, 2017)
Several researches were conducted to explain the financial statement disclosure categorized in to the disclosure research in general and the research examining disclosure of specific aspect, such as the research explaining the effect of Good Corporate Governance (GCG). This research aims to examine the disclosure on specific aspect, voluntary disclousure of GCG in annual report and the relation between the amount of Board of Commissionersand firm value. The population in this research is the manufacturing company registered in Indonesia stock exchange in 2015, in which there are 53 companies as the samples of research. The hypothesis testing was performed with path analysis. The research shows the result that there is significant positive effect in amount variable of Board of Commissioners on the voluntary GCG disclosure and there is no indirect rela tion of Board of Commissioners variable on firm value through voluntary GCG disclosure.Key Words: Good Corporate Governance, voluntary, board of director, firm value